Joel Schreiner: capstone - Schreiner, Joel, artist and filmmaker (Colorado State University. Libraries, 2019)
The artist's statement: For the past four years of education, most of my work has revolved around the betterment of my skills and developing tangible pieces of stories. I have been working towards bringing these stories to life for the past six years through writing, drawing, and designing in order to bring it to life outside of the pages. So far, it has been slow work but the results have been very worthwhile. All of these have come to be through multiple medias due to the journey in becoming an art education major. While not all of my work has embodied these stories, most have been inspired from them. The stories being two: the Revelation series and the Spirit Hunter series. Most of my work has taken from the Revelation series while only a few recent ones have been pulled from the Spirit Hunters series. Revelation follows the story of a young snow leopard, who has lost his memories of home and has been relocated to a western village called Oak-tree. After spending seven years in this region, he recovers most of his memories and begins the journey back home while dealing with the events developing in Verona. Each piece has either taken from a specific moment planned in the series or reflects an item, place, or idea that is present in the story. Spirit Hunters has only recently come back in to rotation of development, but one piece was derived from the story of love and being forgotten that is presented in the series. Many of my works have involved several different ways of planning and making processes, but they all began within the pages of the stories and sketches within a book. Before beginning any of these projects, as well, I make sure I know their place within the story so that it's not just crammed in there. For something to exist outside of the story, it needs to be within reason and have a connection to what has been and will be written. Otherwise, it will seem odd and out of place within the range of its origin. The work I make that relates to these stories must have its place before coming to be. When these come to be, they become part of the living story as a part of its tapestry. While they may not relate to one another directly, they all relate to the world of the story that the works come to exist in. My work represents the stories of Revelation and Spirit Hunters, but it also represents my desire to keep imagination and creativity alive. Anymore, people I encounter struggle to keep these aspects alive and/or in their lives. If I can impart pieces of my imagination into my work, then perhaps others will be able to experience the wonders of another world bringing to life stories of their own. That is the goal of what I want my work to bring to people-becoming a door for which they enter to see a world that they can create stories from. That is what my work means to me and what it represents.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
"Imre de Nueoteric" has no audio; Transcrypted has no spoken word.
Zip files contain: Asset bundles for video creation.
Keywords: electronic art